IMPLEMENTASI NILAI NASIONALISME MELALUI KEGIATAN PRAMUKA - Chania, Ira; Witri, Gustimal; Putra, M. Jaya Adi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to uncover the process of cultivating the values the bacterium through the Boy Scout extracurricular. This research is a descriptive study with a qualitative approach. The research subjects used in this study were 47 Scout students. Data were collected using interviews, observation, and documentation. Data analysis was carried out qualitatively through data reduction, data presentation, and drawing conclusions. The results showed that the implementation of nationalism character values had been carried out through Scout extracurricular activities which contained interesting, challenging, and creative activities. The inculcation of nationalism character values has received support from school culture, school programs, and available facilities. In addition there are also obstacles in the implementation of activities such as, lack of interest from students, different character of students, and lack of firmness from Scout coaches.Key Words: Scouts; Character of student nationalism.